STUDY ON THE FISH SPECIES’S COMPOSITION OF SILURIFORMES IN THU BON – VU GIA RIVER, QUANG NAM PROVINCE - Anh, Vũ Thị Phương; Phú, Võ Văn (Vietnam Journal of Science and Technology, 2012)
SUMMARY Species is composition of the fishes belonging to Siluriformes in Thu Bon – Vu Gia river has a quite biodiversity. The Siluriformes have 16 species belonging to 10 genus and 6 families. Among which, the Clariidae is the most plentiful one’s with 4 species. Siluridae and Bagridae with 3 species. Cranoglanidae, Bagaridae and Ariidae with 2 species.